SARS-CoV-2 in water services: Presence and impacts. (1st January 2021) - Langone, M.; Petta, L.; Cellamare, C.M.; Ferraris, M.; Guzzinati, R.; Mattioli, D.; Sabia, G.
Abstract: The occurrence of human pathogenic viruses in aquatic ecosystems and, in particular, in internal water bodies (i.e., river, lakes, groundwater, drinking water reservoirs, recreational water utilities, and wastewater), raises concerns regarding the related impacts on environment and human health, especially in relation to the possibility of human exposure and waterborne infections. This paper reviews the current state of knowledge regarding severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) presence and persistence in human excreta, wastewaters, sewage sludge as well as in natural water bodies, and the possible implications for water services in terms of fecal transmission, public health, and workers' risk. Furthermore, the impacts related to the adopted containment and emergency management measures on household water consumptions are also discussed, together with the potential use of wastewater-based epidemiology (WBE) assessment as a monitoring and early warning tool, to be applied in case of infectious disease outbreaks. The knowledge and tools summarized in this paper provide a basic information reference, supporting decisions makers in the definition of suitable measures able to pursue an efficient water and wastewater management and a reduction of health risks. Furthermore, research questions are provided, in order to direct technical and public health communities towards a sustainable water service management in the event of a SARS-CoV-2 re-emergence, as well as a future deadly outbreak or pandemic. Graphical abstract: Image 1 Highlights: Increased awareness of the risk of fecal-oral transmission of COVID-19. Importance of addressing risks in SARS-CoV-2 transmission in water services. SARS-CoV-2 presence in wastewater can be used to monitor COVID-19 in a community. The outlined framework provides a knowledge basis for the risk assessment in water services. Abstract : The current knowledge on the SARS-CoV-2 in water services has been reviewed. The main challenges related to an efficient water and wastewater management have been discussed in order to guarantee public health and reduce risks during future deadly outbreak or pandemic.